2001
DOI: 10.1016/s0379-0738(00)00478-3
|View full text |Cite
|
Sign up to set email alerts
|

Online reference database of European Y-chromosomal short tandem repeat (STR) haplotypes

Abstract: The reference database of highly informative Y-chromosomal short tandem repeat (STR) haplotypes (YHRD), available online at http://ystr.charite.de, represents the largest collection of male-speci®c genetic pro®les currently available for European populations. By September 2000, YHRD contained 4688 9-locus (so-called``minimal'') haplotypes, 40% of which have been extended further to include two additional loci. Establishment of YHRD has been facilitated by the joint efforts of 31 forensic and anthropological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 10 publications
2
123
0
5
Order By: Relevance
“…The most common European haplotype, 14-(11,14)-13-16-24-11-13-13, is found in 3.1% of 9972 individuals in the Y-STR HRDatabase [17]. This haplotype was found at 5.4% in the European-American sample.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The most common European haplotype, 14-(11,14)-13-16-24-11-13-13, is found in 3.1% of 9972 individuals in the Y-STR HRDatabase [17]. This haplotype was found at 5.4% in the European-American sample.…”
Section: Discussionmentioning
confidence: 96%
“…There are shared Y-STR haplotypes in populations because either males share identity by descent or because a particular set of Y-STRs does not distinguish closely related, but different, paternal lineages. In a sample of 41 European populations the discrimination capacities were 52% (n ¼ 4688 individuals) and 71% (n ¼ 1957 individuals) using the minimal and extended sets of Y-STRs, respectively [17]. The discrimination capacity in the Iberian Peninsula study [15] was 83% using 19 Y-STRs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These loci form the core set included in the YHRD Database. 32 Extended search in this database (which currently reports 52 655 haplotypes in a worldwide set of 464 populations) shows that the allelic frequencies in the Sicilian sample and Europeans do not differ significantly, with the exception of the DYS391 locus: in Sicily, the nine repeat allele occurs at a frequency of 11.7%, whereas it is very rare elsewhere in Europe; on the other hand it occurs in Tunisia at a frequency of 40%. 23 The DYS445 microsatellite that normally shows an allele of 11 -12 repeats has been observed with a deletion (only six repeats are present) in the J2 Hg.…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…It has been demonstrated that Slavic Y-STR haplotype paternal lineages form a separate branch of the phylogenetic tree of European populations (Roewer et al, 2001(Roewer et al, , 2005. Various parts of Slovakia have different times belonged to the Samos Empire (the first known political unit of Slavs), Great Moravia, the Habsburg (Austrian) monarchy, the Austro-Hungarian monarchy and Czechoslovakia.…”
Section: Introductionmentioning
confidence: 99%